Chemical composition of snow drift on Mizuho Plateau - Osada, Kazuo; Ohmae, Hirokazu; Nishio, Fumihiko; Higuchi, Keiji; Kanamori, Satoru (National Institute of Polar Research, 1989)
P(論文) The chemical composition was determined on snow drift which was sampled at Mizuho Station (2230m a. s. l.) and Mizuho Plateau (1800-3000m a. s. l.), East Antarctica, in 1986. Na^+, Cl^-, NO_3^- and SO_4^<2-> were determined by ion chromatography on 44 samples. Electroconductivity and H^+ concentration were also measured on 85 samples. The concentrations of NO_3^- and SO_4^<2-> of snow drift showed maximum values in summer. It is considered that the concentrations of both Na^+ and Cl^- of snow drift during winter are dependent on not only the amount of sea-salt in the atmosphere but also on the dilution effect through mixing with falling snow. It is pointed out that increase in their concentrations of snow drift in late summer results from aerosol scavenged by drifting snow particles rather than sublimation of drifting snow particles. departmental bulletin paper